Development of sustainable cattle rearing in silvopastoral systems in Latin America - Murgueitio, E.; Chará, J.; R., Barahona; Rivera, J. E. (Cuban Journal of Agricultural Science, 2009)
Tropical and subtropical regions of Latin America, due to their wide territorial extension with lower human population density than Asia and with an accelerated concentration of their inhabitants in the cities, enjoy less limiting agroclimatic conditions than a great part of Africa and Australia in such a way that they are called upon to supply a growing portion of the world demand for bovine, ovine, caprine and buffalo meat, and possibly also for bovine milk. It is predicted that this demand will continue to rise in the next decade (Steinfeld et al. 2006). Forage production, naturally and economically performed, is the basis of the feeding of the se domestic herbivores. An essential condition for this potential to be achieved one day is that small, medium and large scale producers strictly apply the agroecological principles in soil management, water care, and sustainable production of forage biomass and biodiversity conservation (Calle et al. 2013). But, in addition, it is mandatory to guarantee the welfare of animals (Broom et al. 2013), and that production systems reduce greenhouse gas emissions, while being more resilient to climate change effects (Montagnini et al. 2013, Gerber et al. 2013 and Chará et al. 2017).